2015
DOI: 10.1186/s13643-015-0046-y
|View full text |Cite
|
Sign up to set email alerts
|

Interventions targeted at primary care practitioners to improve the identification and referral of patients with co-morbid obesity: a realist review protocol

Abstract: BackgroundObesity is one of the most significant public health challenges in the developed world. Recent policy has suggested that more can be done in primary care to support adults with obesity. In particular, general practitioners (GPs) and practice nurses (PNs) could improve the identification and referral of adults with obesity to appropriate weight management services. Previous interventions targeted at primary care practitioners in this area have had mixed results, suggesting a more complex interplay bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The final stage of analysis involved configuring these CMO patterns into a coherent and plausible “refined” programme theory. As part of the process, several theoretical frameworks that could inform our data interpretation and synthesis were reviewed . From this, a “best fit” theory—candidacy theory—was identified and used to inform the final programme theory.…”
Section: Methodsmentioning
confidence: 99%
“…The final stage of analysis involved configuring these CMO patterns into a coherent and plausible “refined” programme theory. As part of the process, several theoretical frameworks that could inform our data interpretation and synthesis were reviewed . From this, a “best fit” theory—candidacy theory—was identified and used to inform the final programme theory.…”
Section: Methodsmentioning
confidence: 99%
“…4,22,23 The qualitative component of the 5As Team study is similarly unique compared to the existing qualitative literature on primary care providers and obesity management. Past studies focused on providers' self-reported barriers to obesity management, 3,24,25 assessment of providers' existing obesity management ability, 26,27 providers' views on the utility of obesity management interventions, 28 and providers' biases regarding weight and attitudes toward obesity management. 29 The current literature does not describe processes of provider change and development for supporting obesity management in response to an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…18 The central role of the primary health care practitioners (general practitioners and practice nurses) has been acknowledged in the United Kingdom and Scotland, resulting in the formulation of guidelines on overweight/obesity prevention and management at primary care level. 19 The advantage of this strategy is the population coverage and continuity of care and trust built over a number of encounters, 20 and the practical application of the primary care principle that every patient encounter should be regarded as an opportunity for health promotion. 21 The Royal College of Physicians in the United Kingdom has issued a report on the training of general practitioners in weight management.…”
Section: Introductionmentioning
confidence: 99%
“…19 In a study comparing weight bias in 2001 versus 2013 in the management of overweight and obesity among weight management specialists, it was demonstrated that there has been a paradigm shift from implicit (unconsciously expressed) to explicit (consciously expressed) anti-fat bias. The biases were expressed by the medical practitioners as bad, lazy, stupid and worthless.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation